Analisis Standar Pengelolaan Pendidikan - nurhasan (STIT Sirojul Falah Bogor, 2022)
The management standard is one of the national education standards that regulates the planning, implementation, and supervision of educational activities starting from the level of the education unit to the national level, so that the efficiency and effectiveness of education providers can be achieved. Management Standards are national education standards relating to planning, implementation, and supervision of educational activities at the level of education units, districts/cities, provinces, or nationals in order to achieve efficiency and effectiveness in the administration of education. National education standards PP No. 13 of 2015 includes; content standards, process standards, lumusun competency standards, educators and education personnel standards, infrastructure standards, management standards, financing standards and assessment standards. The fields of school management are management of curriculum and learning, management of students, management of educators and education staff, management of facilities and infrastructure, management of finances/financing, management of school relations with schools. Management of education in schools is defined as the process of utilizing school resources through planning, organizing, actuating and controlling activities effectively and efficiently with all its aspects by using all available potential in order to achieve organizational goals. effectively and efficiently as well as quality school productivity. Efforts to achieve these goals are pursued through a